Women As The Catalyst Of Human Capital Development: A Case Study In Malaysia - Abd Jalil, Borham; Munira, Abdul Razak (ARF Publication Sourcing, Islamabad, Pakistan, 2013)

(untitled)
Human Capital can be defined as a measure of the economic value of an employee skill set. This measure builds on the basic production input of labour measure where all labour is thought to be equal (regardless gender) (Becker, 1993). The concept of human capital recognizes that not all labor is equal and the quality of employees can be improved by investing in them. The education, experience and abilities of employee have an economic value for employers and for the economy as a whole. Drucker claims that the greatest challenge for organization is to respond from an industrial to knowledge economy (Drucker, 1985). This shift towards knowledge as the differentiator (rather than gender) affects all aspects of organizational management including operating efficiency, marketing, organizational structure and human capital investment. This study highlights the role of women with competitive values as the catalyst of human capital development in Malaysia.